Meningkatkan Pemahaman Konsep Mahasiswa Pendidikan Fisika Terhadap Materi Efek Fotolistrik - Ayu Masrani Manalu; Cinta Aurelia Sinaga; Ratna Anggi Patra Hs (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research aims to increase Medan State University physics education students' understanding of the concept of the photoelectric effect through the use of the PhET Colorado virtual laboratory. The concept of the photoelectric effect is often a challenge due to its abstract nature and limited laboratory facilities in educational institutions. The research method used was in-depth interviews with three sixth semester physics education students to identify their understanding. The research results show that the virtual laboratory is able to visualize difficult scientific concepts with interactive simulations, significantly increasing student understanding. However, several limitations such as less realistic data availability and limited metal types need to be considered. These simulations provide an engaging, safe, and economical learning experience, and provide an innovative alternative to conventional teaching methods. It is recommended that lecturers receive training in using virtual laboratories and develop supporting modules to maximize the benefits of this media in physics learning.